Mapping Technology Based Tools of Audience Engagement - Jurėnė, Skaistė; Krikščiūnienė, Dalia (Information & Media, 2020)
In order to survive or adapt to new tendencies, cultural organisations must enhance audience engagement. This article proposes a new look at the concept of audience engagement from an integral point of view evaluating and analysing it by means of the conception of a map. The prototype of mapping audience engagement tools created in this article can help cultural organisations to effectively measure and evaluate actions in order to coordinate and select effective audience engagement tools. The empirical part of the article introduces a study of 18 Kaunas City (Lithuania) cultural organisations which reveals that organisations mostly focus on online activities, especially in the categories of accessibility and cognition, and there is a lack of collective development and more active audience engagement in programme development as well as promotion of discussions and original additional context.